GAMBARAN TATA CARA PENGELUARAN SPUTUM DAN KUALITAS SPUTUM PASIEN CURIGA TUBERCULOSIS DI PUSKESMAS GAJAH II KABUPATEN DEMAK - Nani Eko Setiyoningsih; dr. M Sakundarno Adi, MSc. PhD (Dian Nuswantoro Semarang, 2020)
Although the Indonesian government has conducted various efforts to prevent and deal with Tuberculosis disease, new TB cases consistently appear from time to time in this country. Accurate steps and techniques are needed to diagnose tuberculosis as early as possible, thereby reducing transmissions and curing patients as early as possible. One method to conduct early diagnosis of tuberculosis is the microscopic screening of Mycobacteriu Tuberculosa.The purpose of this journal is to get an overview of sputum removal procedures and sputum quality of TB suspects at Gajah II Public Health Centre, Demak District. The first method is spontaneous expectoration, and the second method is warm steam inhalation before sputum removal.In this study, the sputum samples were taken from 32 TB suspect patients who visited Gajah II Public Health Centre for the first time during the period of September 2019. The examination results of sputum quality were recorded into three (3) categories or groups, namely: (1) purulent, (2) mucopurulent, and (3) saliva. The study indicated as follows: using the first method, 2 (two) patients (6.25%) produced purulent quality of sputum, 8 (eight) patients (25%) with mucopurulent quality, and 13 (thirteen) patients (40.62%) with salivary quality, while 9 (nine) patients (28.13%) failed to produce sputum. Using the second method, by which patients were asked to inhale warm steam before removing sputum, the study revealed the following: 3 (three) patients (9.37%) with purulent sputum quality, 13 (thirteen) patients (40.62%) with mucopurulent quality, and 11 (eleven) patients (34.37%) with salivary quality, while 5 (five) patients (15.62%) failed to produce sputum.From the above, using the spontaneus expectoration or first method, most patients produced poor quality of sputum while using the second method, by which patients were asked to inhale warm water vapor before removing sputum, the patients produced improved quality of sputum for smear examination.Keywords: Tuberculosis, sputum quality, Mycobacterium Tuberculosis screening.